1994
DOI: 10.1016/0010-2180(94)90119-8
|View full text |Cite
|
Sign up to set email alerts
|

Laser ignition of pulverized coals

Abstract: We present a novel experiment to study the ignition of pulverized ooal. A dilute stream of panicles is dropped inlo a laminar, upward-flow wind lunnel with a quartz lest section. lbc gas stream is not preheated, A single pulse from a Nd:YAG laser is fotused through the tunnel and ignites the fuel. The transparent test section and cool walls allow for optical detection of the ignition process. In this article we describe the experiment and demonstrate ilS capabilities by ohserving the ignition behavior of spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
12

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 18 publications
2
21
0
12
Order By: Relevance
“…For simplification, single-particle studies were often taken [e.g., [1][2][3][4][5][6][7][8][9][10][11]. Some of them experimentally obtained a large amount data on the ignition temperature and ignition time, and some of them developed ignition models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplification, single-particle studies were often taken [e.g., [1][2][3][4][5][6][7][8][9][10][11]. Some of them experimentally obtained a large amount data on the ignition temperature and ignition time, and some of them developed ignition models.…”
Section: Introductionmentioning
confidence: 99%
“…However, nearly all of them neglected the influence of natural convection while the results were directly compared with experimental data obtained at 1-g in the presence of natural convection. Obviously, this kind of manipulation, though convenient, could induce noticeable discrepancy, especially for large coal particles with diameter larger than 1 mm [5,8]. One important reason to cause this mismatch was due to lack of experimental data at l-g. As introduced, experimental data, even with questionable accuracy were only available after 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Object of this chapter is to develop a model to predict lean flammability limit and flame propagation velocity for pulverized solid fuels, and to apply the model to engineering design for burner systems. Figure 3 shows a schematic of the laser ignition equipment [10][11][12]25]. Uniformly sized pulverized coal particles were suspended in a laminar upward flow and rapidly heated by a single-pulsed YAG laser.…”
Section: Ignition and Flame Propagation Phenomena For Pulverized Coalmentioning
confidence: 99%
“…Fujita et al [8] examined the effect of surrounding oxygen concentration and pressure on flame propagation velocity, while Suda et al [9] examined flame propagation velocities for oxy-fuel combustion conditions. Chen et al [10] and Taniguchi et al [11] developed laser ignition equipment to examine flame propagation velocity of pulverized coals. As well, Taniguchi et al [12] examined the relationship between flame propagation velocity and lean flammability limit for various coals.…”
mentioning
confidence: 99%
“…Previous studies showed that this process is influenced by a few factors, including coal type (Annamalai and Durbetaki 1977;Karcz et al 1980;Tognotti et al 1985;Gieras et al 1986a, b;Essenhigh et al 1989;Gururajan et al 1990;Du and Annamalai 1994;Zhang and Wall 1994;Chen et al 1994;Davini et al 1996;Katalambula et al 1996Katalambula et al , 1997aYang et al 2005), particle size (Annamalai and Durbetaki 1977;Karcz et al 1980;Tognotti et al 1985;Gieras et al 1986a, b;Essenhigh et al 1989;Gururajan et al 1990; Du and Annamalai 1994;Zhang and Wall 1994;Chen et al 1994;Davini et al 1996;Katalambula et al 1996Katalambula et al , 1997a, oxygen concentration (Annamalai and Durbetaki 1977;Karcz et al 1980;Tognotti et al 1985;Gieras et al 1986a, b;Essenhigh et al 1989;Gururajan et al 1990;Zhang and Wall 1994;Chen et al 1994), heating rate (Gieras et al 1986b;Essenhigh et al 1989;Gururajan et al 1990;Du and Annamalai 1994;Zhang and Wall 1994;Katalambula et al 1997b;…”
Section: Introductionmentioning
confidence: 99%